2022
DOI: 10.3390/ijms23105411
|View full text |Cite
|
Sign up to set email alerts
|

A Glimpse of Molecular Biomarkers in Huntington’s Disease

Abstract: Huntington’s disease (HD) is a devastating neurodegenerative disorder that is caused by an abnormal expansion of CAG repeats in the Huntingtin (HTT) gene. Although the main symptomatology is explained by alterations at the level of the central nervous system, predominantly affecting the basal ganglia, a peripheral component of the disease is being increasingly acknowledged. Therefore, the manifestation of the disease is complex and variable among CAG expansion carriers, introducing uncertainty in the appearanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 156 publications
0
16
0
Order By: Relevance
“…The application of single-molecule assay made the quantification of Nfl possible and reliable in blood samples first in 2015 [ 71 ]. And after that, the role of peripheral Nfl level as a potential robust biomarker for HD has been investigated extensively and profoundly [ 72 , 73 ]. As plasma Nfl is widely supposed to be originated from CNS neuronal injuries and associated with CSF Nfl level [ 71 , 74 – 76 ], it is quite valuable and encouraging for a peripheral biofluid biomarker to reflect central pathogenesis, paving the way for its future presumable application in stratifying HD mutation carriers through identification of particular disease stage, especially for premanifest patients, reflecting or even predicting the neuropathological and clinical progression and indicating the therapeutic effect as an outcome measure of clinical trials.…”
Section: Neuronal Injury and Death Biomarkers (Table 1 ...mentioning
confidence: 99%
“…The application of single-molecule assay made the quantification of Nfl possible and reliable in blood samples first in 2015 [ 71 ]. And after that, the role of peripheral Nfl level as a potential robust biomarker for HD has been investigated extensively and profoundly [ 72 , 73 ]. As plasma Nfl is widely supposed to be originated from CNS neuronal injuries and associated with CSF Nfl level [ 71 , 74 – 76 ], it is quite valuable and encouraging for a peripheral biofluid biomarker to reflect central pathogenesis, paving the way for its future presumable application in stratifying HD mutation carriers through identification of particular disease stage, especially for premanifest patients, reflecting or even predicting the neuropathological and clinical progression and indicating the therapeutic effect as an outcome measure of clinical trials.…”
Section: Neuronal Injury and Death Biomarkers (Table 1 ...mentioning
confidence: 99%
“…Genetic analysis of saliva involves the identification and quantification of specific genetic markers or variations in saliva samples. These genetic biomarkers or variations are typically identified and quantified using techniques such as polymerase chain reaction (PCR) or next‐generation sequencing. Inherited disease biomarkers : Inherited genetic mutations can lead to the development of diseases such as cystic fibrosis, sickle cell anemia, and Huntington's disease 89 . Salivary genetic biomarkers have been investigated as a potential tool for diagnosing and monitoring these inherited diseases. Cancer biomarkers : Salivary genetic biomarkers have been investigated as a potential tool for diagnosing and monitoring cancers.…”
Section: The Nature Of Salivamentioning
confidence: 99%
“…Inherited disease biomarkers : Inherited genetic mutations can lead to the development of diseases such as cystic fibrosis, sickle cell anemia, and Huntington's disease 89 . Salivary genetic biomarkers have been investigated as a potential tool for diagnosing and monitoring these inherited diseases.…”
Section: The Nature Of Salivamentioning
confidence: 99%
“…Recent studies have also identified potential biomarkers for other neurodegenerative diseases, such as amyotrophic lateral sclerosis (ALS), Huntington’s disease, and multiple sclerosis These biomarkers include glial fibrillary acidic protein and myelin essential protein, which are indicative of neuronal damage, inflammation, and demyelination, respectively , …”
Section: Biomarkers and Conventional Diagnostics Techniques In Cardio...mentioning
confidence: 99%